2022
DOI: 10.3389/fneur.2022.931437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MMP2 rs243849 and rs14070 genetic polymorphisms on the ischemic stroke susceptibility in Chinese Shaanxi population

Abstract: BackgroundIschemic stroke (IS) is a complex neurological disease affected by genetics and environment. Matrix metalloproteinase-2 (MMP2) is involved in extracellular matrix (ECM) degradation, inflammation and angiogenesis to regulate the development and recovery of IS.PurposesThe aim of this study was to explore the association of rs1053605, rs243849 and rs14070 in MMP2 with the risk of IS in Chinese Shaanxi population.MethodsIn this study, 677 IS patients and 681 normal controls were recruited. Rs1053605, rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The common risk factors for stroke include age, gender, smoking, alcohol abuse, diabetes, hyperlipidemia, and hyperhomocysteinemia [7,8]. In addition to common risk factors, the International Stroke Genetics Consortium states that genetic factors may account for 50% of an individual's risk of stroke and may play a key regulatory role in pathophysiological processes, such as brain cell necrosis and ischemia-reperfusion injury [9][10][11][12]. Therefore, there is an urgent need to further explore the relationship between genetic polymorphisms and IS [13].…”
Section: Introductionmentioning
confidence: 99%
“…The common risk factors for stroke include age, gender, smoking, alcohol abuse, diabetes, hyperlipidemia, and hyperhomocysteinemia [7,8]. In addition to common risk factors, the International Stroke Genetics Consortium states that genetic factors may account for 50% of an individual's risk of stroke and may play a key regulatory role in pathophysiological processes, such as brain cell necrosis and ischemia-reperfusion injury [9][10][11][12]. Therefore, there is an urgent need to further explore the relationship between genetic polymorphisms and IS [13].…”
Section: Introductionmentioning
confidence: 99%
“…At present, a meta-analysis showed that MMP-9 and MMP-12 gene polymorphisms may be risk factors for IS, whereas MMP-1, MMP-2 , and MMP-3 were not associated with the risk of IS ( 15 ). Moreover, the latest study has found that rs243849 and rs14070 in MMP-2 are significantly related to the risk of IS in the Shaanxi population from China ( 16 ). However, no significant association between MMP-9 genetic variants and intracerebral hemorrhage (ICH) susceptibility was reported ( 17 ).…”
Section: Introductionmentioning
confidence: 99%